Changes in body mass and hydration status in judo athletes before and after a top-level competition: a descriptive case study - Ceylan, B.; Barley, O. R.; Balci, S. S. (The Physician and Sportsmedicine, 2023)
Objectives The International Judo Federation (IJF) implemented new regulations in an attempt to regulate rapid weight loss in 2013. The body weight of the athletes cannot be more than 5% higher than the upper limits of their weight categories at the weight check for randomly selected athletes from each weight category before the competition. However, therea lack of studies demonstrating rapid weight loss and hydration status of elite judo athletes in a real match atmosphere under the current refereeing rules. Thus, this study aimed to examine the body mass and hydration changes of elite judo athletes a week before the competition, official weigh-in, and 24 hours after competition.